A comparative study of ectopic pregnancy at a tertiary care centre - Pusuloori, Radhika; Arora, K. Dilzith (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Ectopic pregnancy is a global problem and is the most common life-threatening emergency in early pregnancy leading to significant morbidity and fetal loss. It occurs in variable presentations. The rate of ectopic pregnancies has increased from 0.5% in 1970 to 2% today. The aim of this study was to determine the incidence, clinical presentation, risk factors, treatment, and morbidity and mortality associated with ectopic pregnancy. Methods: The present retrospective study was conducted over a period of three years in the Department of Obstetrics and Gynecology at Chalmeda Anandarao Institute of Medical Sciences, Karimnagar, Telangana from February 2014 to January 2017. A total of 80 patients with ectopic pregnancy were analyzed regarding clinical presentation, risk factors, operative findings and treatment modality. Results: Total number of 80 cases of ectopic pregnancies were admitted during this period against 2645 deliveries representing frequency of 3%. Majority of cases (43.75%) were in the age group of 25-29 years and 41.25% were gravida 4 and above. Risk factors were identifiable in 66.25% of cases. Previous abortion was the most common risk factor (31.25%). The classical triad of amenorrhea, pain abdomen and vaginal bleeding was present in 71.25% of cases. More than half of case (55%) had ruptured tubal pregnancy on admission. Unruptured tubal pregnancy was seen in 10% case. Interestingly we found one rare case of bilateral ectopic pregnancy. Salpingectomy by open method was the mainstay of treatment (86.25%). Conclusions: Ectopic pregnancy is still a major challenge in gynecological practice. In our country most of the cases present late after tubal rupture requiring radical surgical treatment. Early diagnosis and timely intervention in the form of medical treatment or conservative surgery not only reduces maternal morbidity but also preserves future fertility.